FROM COLONIAL SERVITUDE TO CONTEMPORARY MARGINALISATION: EXPLORING THE STRUGGLES OF ASSAM’S ADIVASIS AND TEA GARDEN WORKERS - Nath, Chandamita; Kumar, Sudesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the social stratification and segmentation observed in Assam, focussing on the marginalised groups that face numerous challenges. It specifically addresses the conditions of labourers who were brought to Assam during the colonial period and who have continued to experience conditions resembling servitude within the industry. Despite having lived in Assam for multiple generations, these labourers continue to struggle for recognition of their rights and identity. Often identified as Adivasis or Saah Baganias, they remain side-lined by the indigenous communities of Assam. This research aims to bring attention to these issues, examining how these labourers remain confined by colonial-era